Translating and Validating the Community of Inquiry Survey Instrument in Brazil - Parulla, Cibele Duarte; Weissheimer, Anne Marie; Santos, Marlise Bock; Cogo, Ana Luísa Petersen (International Review of Research in Open and Distributed Learning, 2022)
Massive open online courses (MOOCs) have emerged as an affordable way to distribute knowledge and democratize education. The examination of online courses calls for theoretical models and instruments that contemplate its particularities. The community of inquiry (CoI) framework has been used in several studies to analyze the effectiveness of online education and hybrid education, including MOOCs. This study aimed to translate and validate the Community of Inquiry Survey instrument (Arbaugh et al., 2008) into Brazilian Portuguese, and used a two-stage methodological design for translating and validating a questionnaire. In the first stage, we carried out translation, back-translation, and cross-cultural adaptation. We translated the 34 items while maintaining the survey’s original format. In the expert evaluation phase, all items were considered understandable and essential for inclusion in the Brazilian Portuguese version of the CoI instrument. In the second stage, a prospective cross-sectional study was conducted to validate the questionnaire, and data was collected from participants completing the Nursing Assessment MOOC available on the Lúmina platform. A total of 690 responses were gathered. The resulting instrument produced excellent results, and the three presences achieved high reliability indexes, clearly indicating their adequacy. Furthermore, this study proved the validation of the CoI instrument, maintaining the three-factor structure previously reported in the literature corresponding to the three presences: teaching, social, and cognitive presence. We recommend further studies to evaluate the need for excluding or altering cognitive presence items.